Terrorism: reducing vulnerabilities and improving responses (Washington D.C, 2001)
This book is devoted primarily to papers prepared by American and Russian specialists on cyber terrorism and urban terrorism. It also includes papers on biological and radiological terrorism from the American and Russian perspectives. Of particular interest are the discussions of the hostage situation at Dubrovko in Moscow, the damge inflicted in New York during the attacks on 9/11, and Russian priorities in addressing cyber terrorism.
Keywords: Terrorism